2008
DOI: 10.1051/0004-6361:200809485
|View full text |Cite
|
Sign up to set email alerts
|

VLTI monitoring of the dust formation event of the Nova V1280 Scorpii

Abstract: Context. We present the first high spatial-resolution monitoring of the dust-forming nova V1280 Sco, performed with the Very Large Telescope Interferometer (VLTI). Aims. These observations promise to improve the distance determination of such events and constrain the mechanisms leading to very efficient dust formation under the harsh physical conditions encountered in novae ejecta. Methods. Spectra and visibilities were regularly acquired between the onset of dust formation, 23 days after discovery (or 11 days… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 36 publications
(45 reference statements)
5
58
0
Order By: Relevance
“…Some recent examples suggest that bipolarity in the ejecta of classical/recurrent novae may be relatively frequent: RS Oph (Ribeiro et al 2009;Bode et al 2007;Chesneau et al 2007), V445 Pup (Woudt et al 2009), V1280 Sco (Chesneau et al 2008;Chesneau et al, in prep. ) or HR Del (Harman & O'Brien 2003).…”
Section: A Face-on Bipolar Eventmentioning
confidence: 99%
“…Some recent examples suggest that bipolarity in the ejecta of classical/recurrent novae may be relatively frequent: RS Oph (Ribeiro et al 2009;Bode et al 2007;Chesneau et al 2007), V445 Pup (Woudt et al 2009), V1280 Sco (Chesneau et al 2008;Chesneau et al, in prep. ) or HR Del (Harman & O'Brien 2003).…”
Section: A Face-on Bipolar Eventmentioning
confidence: 99%
“…P-Cygni lines were systematically observed even four years after the outburst, which is indicative of a sustained and significant mass loss (Schwarz et al 2011). The typical P-Cygni type velocities reached 500 km s −1 , from which Chesneau et al (2008) inferred a distance of 1.6 ± 0.4 kpc. However, Hounsell et al (2010) recently derived a distance of 630 ± 100 pc from space-based visual light curves that span the first 20 days after discovery.…”
Section: Introductionmentioning
confidence: 95%
“…Owing to the sparse uv coverage, an interpretation involving a spherical dusty shell was developed, providing estimates of the dust formation rate. Based on an estimate of the total dust mass formed during the 250 days after outburst, Chesneau et al (2008) suggested that a mass as large as 10 −4 M was ejected. Naito et al (2012) provided an independent estimate from neutral oxygen lines that confirmed the high mass ejected, an additional argument for a low-mass WD progenitor, known to statistically eject more mass that fast, massive ones.…”
Section: Introductionmentioning
confidence: 99%
“…Dust has formed in novae where there has been no CO formation. An example is the bright nova V1280 Sco, which formed copious dust (Das et al 2008;Chesneau et al 2008;Chesneau et al 2012), but where no CO emission was detected. NIR spectroscopic observations of V1280 Sco up till the dust forming stage, were taken at high and sufficiently regular cadence to detect CO had it formed notwithstanding its transient nature (Das et al 2008).…”
Section: Early Phase Spectramentioning
confidence: 99%